Varying quantities of alfalfa meal in the rations of spring pigs and in the dry lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
This experiment was conducted the summer of 1955 with spring pigs to obtain information on maximum use of alfalfa meal in protein supplemental mixtures for pigs in the dry lot. Four lots of pigs were self-fed shelled corn and a mixed protein supplement. Lot 1 pigs were placed on sudangrass pasture and self-fed protein supplement made up of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. Lot 2 received the same protein supplement as Lot 1 for 38, days or until they weighed 100 pounds. They were then removed from the pasture and put into a dry lot and red a protein supplement or equal parts tankage and alfalfa meal until the close of the experiment, when they weighed 178 pounds. Lot 3 was fed in the dry lot the entire feeding period on a protein mixture of 4 parts tankage, 4 parts soybean meal, and 3 parts alfalfa meal. Lot 4 was fed in the dry lot the entire feeding period with an increased alfalfa meal allowance, a protein supplement mixture of 5 parts tankage and 5 parts alfalfa meal.
Keywords: Swine; Alfalfa meal; Spring pigs; Dry lot